Dimming the midnight sun? Implications of the Sámi Council's intervention against the SCoPEx project - Oksanen, Aslak-Antti (Frontiers in Climate, 2023)
Indigenous peoples are amongst those most vulnerable to the effects of climate change and any potential environmental effects of geoengineering projects. It is therefore not surprising that the Sámi Council decided to take an open stance on the SCoPEx solar geoengineering research project upon finding out of its planned test flight near Giron/Kiruna, Sweden, in the Sámi people's domicile area. In their open letter to the to the SCoPEx Advisory Committee, the Swedish Space Corporation and the Swedish government, the Sámi Council objected to the lack of any consultations with the Sámi people and the aims of the project, resulting in cancellation of the flight. As the Sámi Council has a strong track record of leadership among indigenous peoples globally, this intervention has implications for the role of indigenous peoples in relation to the question of geoengineering. This paper uses a discourse analytical method to analyse publicly available sources to map out the background for the Sámi Council's intervention against the SCoPEx project and its future implications. It finds that the manner in which the SCoPEx project's test flight was planned on Sámi domicile area, without any consultations, led the Sámi Council to find joint cause with environmental civil society groups opposed to geoengineering. Subsequently, the Sámi Council has taken an active role in rallying further indigenous opposition to the SCoPEx project and by extension geoengineering research. It is argued that this coalition of indigenous peoples' organizations and environmental civil society organizations is premised on a discursive framing of an opposition between nature-based solutions to climate change and, geoengineering as representative of a technological solution that allows extractive capitalism to persist. The Sámi Council's intervention has important humanitarian implications. As indigenous peoples are uniquely vulnerable to any environmental changes resulting from geoengineering, the Sámi Council's intervention and its outcome sets a precedent of indigenous peoples as stakeholders in the geoengineering question, whose views must be respected and interests safeguarded.